2004
DOI: 10.1037/0022-3514.86.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion and Emotional Reactivity.

Abstract: Six mood induction studies and a meta-analysis were conducted to test 2 models of the extraversion-pleasant affect relation. The affect-level model suggests that extraverts should be happier than introverts in both neutral and positive mood conditions. The reactivity model posits that extraverts react particularly strongly to pleasant stimuli and that they should be happier than introverts only in positive conditions. In all studies, extraverts failed to exhibit greater emotional reactivity when pleasantness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
165
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 51 publications
18
165
2
7
Order By: Relevance
“…Two core aspects of extraversion are positive affect and a tendency to seek out and participate in social situations (Lucas and Diener, 2001;Lucas and Baird, 2004). Both these aspects of extraversion are related to hemispheric asymmetries in the PFC, as lesser right vs. left-sided anterior electrophysiological activity is associated with positive affect and approach behaviors (Tomarken et al, 1990;Tomarken et al, 1992;Davidson, 2004bDavidson, , 2004a.…”
Section: Structural Correlates Of Extraversion Across the Age Rangementioning
confidence: 99%
“…Two core aspects of extraversion are positive affect and a tendency to seek out and participate in social situations (Lucas and Diener, 2001;Lucas and Baird, 2004). Both these aspects of extraversion are related to hemispheric asymmetries in the PFC, as lesser right vs. left-sided anterior electrophysiological activity is associated with positive affect and approach behaviors (Tomarken et al, 1990;Tomarken et al, 1992;Davidson, 2004bDavidson, , 2004a.…”
Section: Structural Correlates Of Extraversion Across the Age Rangementioning
confidence: 99%
“…For example, two recent fMRI studies by Canli and colleagues (9,10) showed that extroversion positively correlates with phasic blood oxygenation level-dependent (BOLD) activity in the PFC and amygdala during the presentation of positively valanced faces, whereas neuroticism increases in association with middle temporal and frontal cortical activation during the presentation of negatively valanced faces. Collectively, these observations have led to the hypothesis that extroverts and neurotics are phenomenologically attuned to stimuli of positive and negative emotional significance, respectively (4,7,18).…”
mentioning
confidence: 99%
“…The findings reported herein strongly favor the hypothesis that personality style is a mediating factor in the neurobiological regions known to be involved in humor appreciation and help to resolve inconsistent results from previous neuroimaging studies of this important human phenomenon. mentioned above (4,7,18), we restricted our analysis to extroversion and neuroticism. Resultant T scores were correlated with behavioral data, regions of interest, and whole-brain BOLD signal.…”
mentioning
confidence: 99%
“…However, evidence supporting this hypothesis has been mixed and more recent studies comparing responses of extraverts vs. introverts after having been exposed to natural or laboratory positive stimuli have yielded null results (e.g., Lucas & Baird, 2004;Lucas et al, 2008). Some authors have highlighted the difference between wanting (i.e., reward desire) and liking (i.e., reward enjoyment), and recent data seems to be consistent with the view that extraversion is more associated with wanting than with liking (Smillie, 2013a;Smillie, Cooper, Wilt, & Revelle, 2012).…”
Section: The Core Features Of Extraversionmentioning
confidence: 94%